Noise Level Assessment In Engineering Campus Of Universiti Sains Malaysia A Comparison Before And During Covid-19 Pandemic - Mokti, Nur Syazliana Abd (Universiti Sains Malaysia, 2021)
Noise pollution is a dangerous hazard that is often overlooked. It is invisible to the naked eye, although it exists on land and beneath the water. It may also be described as any undesirable or distressing sound that has an impact on human and other species' health and well-being. Manufacturing, development, transportation, and community and home activities have all produced many types of noise in modern life. This research was conducted to investigate the noise level and sources of noise in the USM Engineering Campus. Besides, this study was carried out to compare the changes of noise level due to the Covid-19 Pandemic. The sound level meter, manual traffic count, and laser speed gun were used to measure noise and traffic. The mapping was analysed using ArcMap 10.3. From the results, from both situations; before and during the Covid-19 Pandemic some of the equivalent noise levels on the campus exceeded the permissible noise levels allowed by Department of Environment (DOE). However, the World Health Organization (WHO) limits (55dB(A)), it is found that noise levels before the Covid-19 Pandemic exceeded higher than during the Pandemic. Apart from that, from the research, it is revealed that noise level of A-weighted Equivalent Noise Level, LAeq having an average reduction of positive 6dB(A). Last but not least, producing noise mapping, can aids in the development of a better knowledge of acoustic settings and the problem of noise pollution in the environment.